2012
DOI: 10.1186/2045-709x-20-23
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spinal manipulative therapy on spinal range of motion: a systematic literature review

Abstract: BackgroundSpinal manipulative therapy (SMT) has been shown to have an effect on spine-related pain, both clinically and in experimentally induced pain. However, it is unclear if it has an immediate noticeable biomechanical effect on spinal motion that can be measured in terms of an increased range of motion (ROM).ObjectiveTo assess the quality of the literature and to determine whether or not SMT is associated with an immediate increase in ROM.DesignA systematic critical literature review.MethodSystematic sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Interestingly, these changes were not associated with changes in lumbo-pelvic kinematics. In a recent review, Millan et al [23] reported that none of the selected studies of the lumbar spine showed an immediate effect of SMT on lumbar range of motions. Future studies should include assessment for an extended period of time (hours and days) in order to better document the association between neuromuscular response to SMT and changes in lumbo-pelvic kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, these changes were not associated with changes in lumbo-pelvic kinematics. In a recent review, Millan et al [23] reported that none of the selected studies of the lumbar spine showed an immediate effect of SMT on lumbar range of motions. Future studies should include assessment for an extended period of time (hours and days) in order to better document the association between neuromuscular response to SMT and changes in lumbo-pelvic kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Of the biological mechanisms, experimental and clinical evidence suggest that manual therapy produces short-term modulation of pain, probably mediated by activation of the descending inhibitory pathways of the CNS [8][9][10][11]. While there is limited clinical evidence supporting immediate increases in spinal range of motion [12][13][14][15][16][17] and influence on posture [16,[18][19][20], additional research is required to determine whether these changes are clinically relevant. It is important to realise that, while basic or primary experimental research may support the plausibility of a variety of mechanisms that produce changes to the tissues or nervous system, there remains a lack of clinical evidence that establishes these changes as relevant and meaningful to clinical outcomes in patients.…”
Section: Therapeutic Mechanisms Of Manual Therapymentioning
confidence: 99%
“…For example, very gentle extensibility and stretching forces are advisable for a strained muscle in the first few days of injury, which can be progressively increased as the sensitivity of the tissue decreases and healing occurs. Passive manual techniques may promote movement [12][13][14][15][16][17] and reduce pain [8][9][10][11] and, combined with reassurance and pain education, encourage the person to perform normal movement patterns and activity ( Figure 1). Active and passive movements create pressure fluctuations within synovial joints [66], which promote trans-synovial flow of fluids across the synovial membrane and stimulate blood flow around the joint [67][68][69].…”
Section: Acute Pain and Movement Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…HVLA techniques produce different effects on the body system: mechanical effects (Triano and Schultz, 1997;Triano, 2001;Millan et al, 2012;Snodgrass et al, 2012) and neurophysiological effects (Pickar, 2002) on the axial muscles (Bicalho et al, 2010;Clark et al, 2011;Koppenhaver et al, 2011;Puentedura et al, 2011) as well as on the peripheral muscles (Herzog et al, 1999;Suter et al, 2000;Hillermann et al, 2006), and on sensitivity (Bialosky et al, 2009;Bishop et al, 2011;Sparks et al, 2013).…”
Section: Introductionmentioning
confidence: 97%